Quantification and Standardized Description of Color Vision Deficiency Caused by Anomalous Trichromats—Part I: Simulation and Measurement. (2nd January 2008) - Yang, Seungji; Ro, Yong Man; Wong, Edward K.; Lee, Jin-Hak
Abstract : The MPEG-21 Multimedia Framework allows visually impaired users to have an improved access to visual content by enabling content adaptation techniques such as color compensation. However, one important issue is the method to create and interpret the standardized CVD descriptions when making the use of generic color vision tests. In Part I of our study to tackle the issue, we present a novel computerized hue test (CHT) to examine and quantify CVD, which allows reproducing and manipulating test colors for the purposes of computer simulation and analysis of CVD. Both objective evaluation via color difference measurement and subjective evaluation via clinical experiment showed that the CHT works well as a color vision test: it is highly correlated with the Farnsworth-Munsell 100 Hue (FM100H) test and allows for a more elaborate and correct color reproduction than the FM100H test.